2009
DOI: 10.3174/ajnr.a1799
|View full text |Cite
|
Sign up to set email alerts
|

Significant Temporal Evolution of Diffusion Anisotropy for Evaluating Early Response to Radiosurgery in Patients with Vestibular Schwannoma: Findings from Functional Diffusion Maps

Abstract: BACKGROUND AND PURPOSE:Outcome evaluation in clinical oncology is conventionally based on long-term volumetric changes in the tumor size. The purpose of this study was to prospectively investigate the usefulness of fDMs in incorporating anisotropic diffusion in the evaluation of early response after radiosurgery in patients with vestibular schwannoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…ADC values may be affected in tissue damage such as edema, degeneration, and necrosis [21]. Radiation-induced changes in the auditory pathways can be detected in patients with VS treated with radiosurgery [6,8,9,22]. In our study, contralateral LL FA values were lower than ipsilateral in the pretreatment period.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…ADC values may be affected in tissue damage such as edema, degeneration, and necrosis [21]. Radiation-induced changes in the auditory pathways can be detected in patients with VS treated with radiosurgery [6,8,9,22]. In our study, contralateral LL FA values were lower than ipsilateral in the pretreatment period.…”
Section: Discussionmentioning
confidence: 44%
“…There was no strong correlation between them. A decrease in FA values may be associated with alterations in cytoarchitecture [22]. The weak relationship between the brainstem radiation dose and the slight decrease in contralateral HG FA values may indicate that no significant permanent damage to the radiation-induced auditory pathways had developed.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on acoustic neuromas (AN), another disease that involves auditory pathways such as NF1, ADC increase was found in lateral lemniscus, colliculus inferior, corpus geniculatum mediale and Heschl's gyrus in AN patients when compared to healthy control subjects and thought to be related to microstructural changes such as dysmyelination or loss of myelin [4]. In another study of patients with sensorineural hearing loss, it was suggested that reduced FA values with increased radial diffusivity in the colliculus inferior and lateral lemniscus caused by the dysmyelination process [15]. In our study, we found that there was an increase in ADC values of the auditory pathways in patients with NF1.…”
Section: Discussionmentioning
confidence: 99%
“…The role of DTI in improving outcomes has been established in both low and high-grade gliomas (HGG), including glioblastomas (GBM), meningiomas, and medulloblastomas. It also serves as an adjunct to the awake craniotomy for tumor resection and radiation planning for stereotactic radiosurgery [ 5 - 8 ].…”
Section: Discussionmentioning
confidence: 99%